Implementasi Penilaian Kinerja dalam Pembelajaran Bahasa Indonesia di SMP Kerumutan, Kabupaten Pelalawan - Yunita, Rika; Sukenti, Desi (Cetta: Jurnal Ilmu Pendidikan, 2024)
Assessment activities are an important aspect in the learning system. Teachers need to carry out assessments both when learning begins and even before learning practice takes place, during the teaching and learning process, or at the end of a learning activity. One of the assessments that must be carried out by Indonesian language teachers is performance assessment. The aim of this research is to describe the implementation of performance assessment in Indonesian language learning at Kerumutan Middle School, Pelalawan Regency and describe the models used in performance assessment in Indonesian language learning. This research is a qualitative descriptive study. The method used in this research is a survey. The population and sample in this research were 4 class VII Indonesian language teachers at Kerumutan Middle School. Data was obtained through questionnaires, interviews and observations. Data collection was carried out using Google Form. Data were analyzed using descriptive statistics with 4 steps, namely: collecting data and carrying out data reduction, calculating the percentage of questionnaire results, presenting data in the form of short descriptions and tables, and data were analyzed and conclusions were drawn. The results of the research show that all teachers have carried out performance assessments in Indonesian language learning at Kerumutan Middle School using various models, namely, listening assessments, picture-based talks, interviews, telling stories, giving speeches, discussing, reading aloud, writing essays, writing scientific papers, news, reports, letters, and analysis of literary texts.